Reimagining CO2 management: SWOT analysis and global outlook on CCUS and ICCU technologies - Sudhakaran, Amitha Kalappurakkal; Sreekantan, Sreejith; Marimuthu, Banu (Sustainable Chemistry for Climate Action, 2025)
<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">The persistent rise in atmospheric CO<span style="box-sizing: border-box; margin: 0px; padding: 0px; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif;">2<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> levels, driven by industrialization and fossil fuel dependence, has made carbon dioxide a central target in global climate mitigation efforts. Despite its thermodynamic stability and linear geometry, which make its activation inherently difficult, CO<span style="box-sizing: border-box; margin: 0px; padding: 0px; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif;">2<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> has long been identified as a major greenhouse gas since the mid-20th century. This review presents a comprehensive outlook on Carbon Capture, Utilization, and Storage (CCUS) technologies, with a focused discussion on Integrated Carbon Capture and Utilization (ICCU) approaches. We begin with a brief historical and scientific background on CO<span style="box-sizing: border-box; margin: 0px; padding: 0px; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif;">2<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> as a greenhouse gas and the pressing need to curb emissions. A critical evaluation of various capture technologies-post-combustion, pre-combustion, oxy-fuel, and direct air capture is provided, highlighting their principles, merits, and limitations. The current global landscape of CCUS infrastructure, including pilot, commercial, and developing-scale operations, is summarized. A SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis is presented to assess the viability of CCUS pathways. Particular emphasis is placed on CO<span style="box-sizing: border-box; margin: 0px; padding: 0px; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif;">2<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> capture mechanisms via absorption (liquid solvents like amines, amino acids, ILs, ammonia, and alkaline solutions) and adsorption (solid sorbents), followed by a detailed literature survey of solvent-based capture methods. Recognizing the isolated inefficiencies of standalone capture or utilization processes, the review underscores the emerging importance of ICCU strategies. Recent advancements in CO<span style="box-sizing: border-box; margin: 0px; padding: 0px; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif;">2<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> conversion to methanol, methane, and formic acid via integrated systems are discussed, highlighting the synergy between capture and conversion units.